Endometriosis resembling endometrial cancer in a postmenopausal patient. (2nd January 2018) - Suchońska, B.; Gajewska, M.; Zyguła, A.; Wielgoś, M.
Abstract: Endometriosis occurs in 2–4% of postmenopausal women. There have been a few reports of endometriosis in women in whom neither history nor diagnostic imaging indicated the presence of this disease, either at reproductive age or after menopause. A case is described of an 84-year-old patient with extensive deep pelvic endometriosis imitating advanced neoplastic process.